1999
DOI: 10.1038/sj.jim.2900693
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Lactobacillus helveticus entrapped in Ca-alginate in relation to water content, storage and rehydration

Abstract: Lactobacillus helveticus CNRZ 303 entrapped in Ca-alginate gel beads was investigated for improved survival and stability during fluidized-bed drying, storage and rehydration. Addition of protective solutes was very important. Studies of the conditions showed that inactivation of entrapped L. helveticus started when the water content exceeded 0.3-0.4 g H2O (g dry wt)-1 for adonitol, glycerol and reconstituted non fat milk solids (NFSM). With Ringer's solution (control) and betaine, the fall in viability was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 26 publications
3
50
0
4
Order By: Relevance
“…Often, the air stream would carry significant heat in order to achieve efficient water evaporation. Factors that are detrimental to the viability of microorganisms include heat stress from the risen temperature, osmotic stress and capillary forces due to the removal of water, oxidative stress from the contact with the oxygen in air, and the increase in intracellular pH and salt concentration due to the loss of water (Santivarangkna, Kulozik, & Foerst, 2008;Selmer-Olsen, Søhaug, Birkeland, & Pehrson, 1999). The resultant heat damage and dehydration damage on cells are two major factors to consider.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the air stream would carry significant heat in order to achieve efficient water evaporation. Factors that are detrimental to the viability of microorganisms include heat stress from the risen temperature, osmotic stress and capillary forces due to the removal of water, oxidative stress from the contact with the oxygen in air, and the increase in intracellular pH and salt concentration due to the loss of water (Santivarangkna, Kulozik, & Foerst, 2008;Selmer-Olsen, Søhaug, Birkeland, & Pehrson, 1999). The resultant heat damage and dehydration damage on cells are two major factors to consider.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the stationary phase cultures are more resistant to heat compare to cells in exponential growth phase [61].One approach used by a number of researchers to improve probiotic survival is the addition of protectants to the media prior to drying. For example, the incorporation of thermoprotectants, such as trehalose [75], non-fat milk solids and/ or adnitol [76], growth promoting factors including various probiotic/prebiotic combinations [77] and granular starch [78] have been shown to improve culture viability during drying and storage [79,80].…”
Section: Spray-dryingmentioning
confidence: 99%
“…Skim milk powder has been reported to preserve cell viability by protecting cells from the abrupt loss of free water and changes in temperature during storage (Burges 1998;Selmer-Olsen et al 1999). PVP is also a useful formulation excipient, as it is a binding powder, can form films, acts as an excellent bulking agent and increases the viscosity (Bühler 2001).…”
Section: Introductionmentioning
confidence: 99%